Disaster communication in managing vulnerabilities - Ravichandran Moorthy,; Guido Benny,; Sarjit S. Gill, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The management of information among various stakeholders in natural and human induced disasters is fundamental to the mitigation and effective disaster-relieve operations. Efficient information exchanges are a vital component of disaster response and relief operations. This is based on the idea that precise and timely information is made available prior, during and after disasters. Disasters always happen abruptly, and often with different levels of severity, posing a major challenge for effective information exchanges and coordination. Extended droughts, trans-boundary haze, earthquakes, floods, hurricanes, tsunamis, landslides, volcanic activities and severe weathers have created havoc and displaced populations in many parts of this continent. These events have given rise to the realization that a more strenuous attempts to uncover the emerging patterns in disaster communication. By drawing from experiences in disasters, especially in Asia, the paper firstly conceptualizes disaster, vulnerabilities and disaster communication, in the broader literature on disaster. Secondly, it examines how the emerging features, such as disaster communication and coordination mechanism, the role of social media and technology, reliability of communication systems, social capital and cultural knowledge can assist first responders, care givers and disaster related agencies in helping disaster victims more effectively.